Targeted inhibition of RAGE reduces amyloid-β influx across the blood-brain barrier and improves cognitive deficits in db/db mice. (15th March 2018) - Wang, Hao; Chen, Fang; Du, Yi-Feng; Long, Yan; Reed, Miranda N.; Hu, Mei; Suppiramaniam, Vishnu; Hong, Hao; Tang, Su-Su
Abstract: Aims: To investigate restorative effects of the receptor for advanced glycation end products (RAGE)-specific inhibitor FPS-ZM1 on abnormal amyloid β (Aβ) influx across the blood brain-barrier (BBB) and cognitive deficits in db/db mice. Methods: Aβ influx across the BBB was determined by intra-arterial infusion of 125 I-Aβ1-40 . Receptor for advanced glycation end products (RAGE), Aβ, NF-κB p65, caspase-3, Bax, Bcl-2, PSD-95 and synaptophysin were assayed by Western blot, immunohistochemistry or RT-PCR. Apoptosis was quantified by TUNEL assay. In vivo hippocampal long term potentiation (LTP) recording, Golgi Staining, Morris water maze (MWM) task and Y-maze test were performed. Results: FPS-ZM1 (1.0 mg/kg i.p. ) inhibited Aβ influx across the BBB and expression of RAGE participating in Aβ influx, consequently decreased hippocampal Aβ1-40 and Aβ1-42 in db/db mice. After FPS-ZM1 treatment, NF-κB signaling was inhibited, and neuronal apoptosis was reduced, which revealed by less TUNEL + cells, reduced caspase-3 activity and higher ratio of Bcl-2/Bax. In addition, FPS-ZM1 improved hippocampal plasticity evidenced by enhanced in vivo LTP and the restoration of spine deficit and increased PSD-95 expression in hippocampal neuron. Further studies found that FPS-ZM1 treatment alleviated cognitive deficits shown by better performance in behavioral tests, without significant metabolic effects on blood glucose, insulin and cerebral AGEs. Conclusion: Downregulation of abnormal Aβ influx across the BBB by FPS-ZM1 at higher dosage contributes to reduced neuronal apoptosis, improved hippocampal plasticity and cognitive impairment in db/db mice. Highlights: Targeted inhibition of RAGE restores abnormal transport of Aβ across the BBB. Targeted inhibition of RAGE reduces Aβ levels in brain of db/db mice. Targeted inhibition of RAGE ameliorates memory impairment in db/db mice. Targeted inhibition of RAGE inhibits neuronal apoptosis and improve hippocampal plasticity.